Processing characteristics and micro-structural evaluation of kilishi under different processing methods (2006)
Kilishi processing is time consuming, rigorous and location specific — the focus of this study was therefore to assess if the effects of using a mechanical slicer (rather than hand slicing) and oven drying (instead of sun drying) would significantly affect the product yield of Kilishi. Two kilogram each of choice trimmed beef was used in two replicates of four treatments in a completely randomized design. Treatments A, B, C, and D represents hand sliced, sun dried samples; mechanically sliced, sun dried samples; hand sliced, oven dried samples and mechanically sliced oven dried samples respectively. Meat used were chilled overnight and processed the following morning. The histological characteristics of muscle tissue used for Kilishi production as affected by drying were studied. For slice thickness, there were no significant differences between the mechanically sliced and hand sliced, sun dried products, but the oven dried products were significantly different (P<0.05). It was observed that the mechanical slicing and oven drying gave the highest yield of 65.21 %, compared to 58.66% yield from the traditional processing method. Light microscopy showed that both intracellular and extra cellular components were affected by the conditions of processing. Mechanical slicing and oven drying in Kilishi production holds an economic advantage to producers who desire higher product yield and a safer product from oven drying for consumers who relish the snack.